Some Tips on Numerical Modeling of Airflow and Fires in Road Tunnels - Aleksander Król (Energies, 2021)
The efficiency of tunnels systems is often evaluated using numerical simulations. This concerns both to normal and emergency mode of tunnel systems operation. Therefore the safety level of tunnel users may depend on the quality of numerical models being built. The most often studied areas cover the researches on natural and forced airflows in the normal mode and on fire development and smoke spreading in the emergency mode as well as modeling of fan operation. Thus, many software packages implementing Computational Fluid Dynamics (CFD) are applied here. Despite the available software is recognized as reliable, the problem arises because the built numerical models should be validated at least partially with experimental data. There is a shortage of experimental data from real tunnels due to high costs and many organizational or formal difficulties. Some researchers use data from scaled experiments, but this leads to problems connected with scaling. The paper presents the application of two widely used software packages—Fire Dynamics Simulator (FDS) and ANSYS Fluent to reproduce some scenarios of the operation of a tunnel ventilation system for normal and emergency mode. Most of results were compared with data obtained by own full scale measurements or data available in literature. Some practical issues concerning the application of FDS and ANSYS Fluent were discussed as well.